The value of Healthcare workers supports techniques to increase wellness and optimise patient care - BASEM MOHAMMED SAED ALQAHTANI, Hajar Ali Mahdi Aljaboari, RASHED YAHYA HASSAN ALGHAZWANI, ALMUTASIM BILLA YAHYA MOHAMMED QAARI, Mohammed Dawood Abdrabuh dhaifallah; Hassan Yahya Muhammad Al-Shahrani, MOHAMMED ABDULAZIZ IBRAHIM ALRAGDI, Muteb Mohammed Ali Alasmary, Ahmed Mousa Mohammed Alasiri, Yahya Abdullah Tala Asiri (Journal of International Crisis and Risk Communication Research, 2024)
The support techniques for healthcare workers play a significant role in promoting their wellness, which directly impacts the quality of patient care. By addressing the mental, physical, emotional, and professional needs of healthcare workers, healthcare organizations can enhance job satisfaction, reduce burnout, and foster a compassionate and efficient workforce. The end result is not only a better working environment for healthcare providers but also improved health outcomes for patientsPatient satisfaction can be defined as perception minus expectation. Dissatisfaction results when a patient’s perception is less than their expectation. Small deeds can have a disproportionate effect on the patient satisfaction equation: time spent with a patient, holding a hand, or an act of kindness and caring all play a part in reducing fear and anxiety, dispelling anger, or offering hope